Reported versus confirmed wheeze and lung function in early life. Issue 6 (21st May 2004) - Lowe, L; Murray, C S; Martin, L; Deas, J; Cashin, E; Poletti, G; Simpson, A; Woodcock, A; Custovic, A
Abstract : Aims: To investigate the relation between parentally reported wheeze (unconfirmed), physician confirmed wheeze, and subsequent lung function. Methods: Children at risk of allergic disease (one parent atopic) were recruited antenatally and followed prospectively from birth. During the first three years of life parents were asked to contact the study team if their child was wheezy. The presence of wheeze was confirmed or not by the primary care or study physician. Respiratory questionnaire and specific airway resistance measurement (sRaw, body plethysmograph) were completed at age 3 years. Results: A total of 454 children were followed from birth to 3 years of age. One hundred and eighty six (40.9%) of the parents reported their child wheezing in the first three years of life, and in 130 (28.6%) the wheeze was confirmed. A total of 428 children attended the three year clinic review, of whom 274 (64%) successfully carried out lung function tests. There was no significant difference in sRaw (kPa·s; geometric mean, 95% CI) between children who had never wheezed (n = 152; 1.03, 1.00 to 1.06) and those with a parentally reported but unconfirmed wheeze (n = 36; 1.02, 0.96 to 1.07, p = 1.00). sRaw was significantly higher in children with a physician confirmed wheeze (n = 86; 1.17, 1.11 to 1.22, p < 0.001) compared to those with no history of wheeze or with unconfirmed wheeze. Conclusions: Children with physician confirmed wheeze have significantly poorer lung function compared to those with parentally reported but unconfirmed and those who have never wheezed. A proportion of parents may have little understanding of what medical professionals mean by the term "wheeze".